PERHITUNGAN STRUKTUR GEDUNG TAHAN GEMPA PADA BANGUNAN HOTEL 12 LANTAI DENGAN SISTEM RANGKA PEMIKUL MOMEN BIASA DI KOTA BATAM - Fauzan Fauzan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Planning for high-rise buildings with the risk of seismicity can be calculated by several methods. Among them are the Moment Bearer Frame System (SRPM) and Structural Wall System (SDS) methods. Indonesia is a country with a high level of seismic activity, one of which is the city of Batam (earthquake zone 1), so the building structure must be planned to be resistant to earthquakes which have been regulated in SNI 03-1726-2012 and SNI 03-2847-2013. Therefore, this final project discusses the optimization of earthquake load-bearing structural systems (lateral, stiffness, structural resistance in 12 floors hotel building. The design of the building structure uses the 2013 ETABS auxiliary program by adjusting the parameters of the strength of the material used. Quality of concrete (f'c = 30MPa) & the quality of reinforcing steel (fy = 400MPa) and gravity loading and earthquake loading of the building structure The upper main portal structure of the building is designed with the concept of capacity, namely strong column weak beam (SCWB), the occurrence of plastic joints at the ends of the beam, column feet and wall legs structural analysis, which is then analyzed the dimensions and pengesiannya due to gravity loads, equivalent static earthquakes and dynamic earthquakes of various response spectrum.From the structural design analysis, the results show that the stiffness, strength and resistance of multiple systems with smaller dimensions and the reinforcement of the structural components of the main portal meet the performance requirements of the structure boundary In the bearer frame system moments can be used where the earthquake load is 100% held at the moment frame, so the size of the beam and column frames will be smaller.